(untitled) (American Journal of Economics and Business Innovation, 2024)
This article delves into the role of Foreign Direct Investment (FDI) in wealth creation in Morocco. The in-depth analysis highlights the economic implications and outcomes of FDI on the country’s economic development. The study emphasizes potential benefits such as job creation, technology transfer, and increased productivity. The research also explores challenges and risks associated with FDI, including the potential dependence on foreign investors and socio-economic inequalities. Concrete examples are provided to illustrate the impact of FDI on key sectors of the Moroccan economy. In conclusion, the article proposes policy recommendations to maximize the benefits of FDI while mitigating risks. It underscores the importance of a balanced and strategic approach to harness the full potential of foreign investments, promote sustainable economic growth, and enhance wealth creation in Morocco. In light of our econometric study on the impact of FDI on wealth creation in Morocco, the findings demonstrate that foreign direct investment (FDI) has played a crucial role in wealth creation in the country. The positive effects of FDI are clearly discernible across various sectors of the economy.